Reaching the community of B40 learners: fun with English - Jalaluddin, Ilyana; Mohamad Ali, Afida; Lee, Geok Imm; Victor Danarajan, Sharon Sharmini; Darmi, Ramiza; Yahya, Muhammad Yasir; Mohd Kasim, Zalina; Chan, Mei Yuit; Chin, Ee Wen; Mohd Kasim, Zalina; Nimehchisalem, Vahid; Yahya, Muhammad Yasir; et al. (UMK PRESS, 2024)
‘Fun with English’ aimed to raise awareness among B40 learners regarding social media and current issues related to youth nowadays. Some of the issues discussed were to work or to further study, future path, online scam, job scam, freedom of expression in online world, body shaming, peer pressure, bullying, celebrity crush, and benefits of e-sports. 250 participants mainly aged 16-17 years from secondary schools in Selangor rural areas were then taught on how to create media-video on the current issues discussed in English language. Here, TikTok was introduced to them. To create more impact by promoting the issues via media, the techniques in video editing and graphic design were taught to the learners. This built the learners’ confidence to create content for public audiences as they were required to act to create the contents and used English language as a medium to convey messages. Public were also invited to give support to these learners and view their works at the end. Some of the learners’ works were also shared by government bodies such as Persatuan Suri dan Anggota Wanita Perkhidmatan Awam Malaysia (PUSPANITA) on public platforms to promote awareness among society.